Opportunity and the sexual abuse of adolescents. (December 2021) - Felson, Richard B.; Savolainen, Jukka; Whichard, Corey; Fry, Sarah; Ellonen, Noora
Abstract: Objectives: The risk of sexual abuse victimization was examined from a routine activity perspective. For comparison, predictors of sexual encounters with same-age peers were also examined. Methods: Analyses were based on a nationally representative sample of 24, 823 Finnish youth who responded to questions about their sexual encounters with peers and with someone outside their family who was at least five years older. Results: Adolescents who had older friends and parents who did not monitor their social relationships were at greater risk of sexual abuse and peer encounters. In addition, delinquent youth had a higher risk of abuse than non-delinquents, controlling for exposure. Delinquent youth were also more likely to have favorable attitudes toward the abuse, to initiate the sexual encounter, and to experience repeat victimizations. Physical attractiveness, but not sexual maturity, was related to abuse. Conclusions: Risk of sexual abuse is positively related to exposure to older people, susceptibility to deviant influence, and the target's value to the offender. A full understanding of risk factors requires a consideration of the victims' characteristics and their compliant behavior.